Sociology as a Basis for Curriculum Development for Islamic Religious Education - Farida Ummami; Khozin (HISTORICAL: Journal of History and Social Sciences, 2024)
The purpose of this article is to explain how sociological foundations are the basis for developing the Islamic religious education curriculum. This article uses qualitative research methods, data collection techniques using library research. Library research includes four stages: preparing necessary documents, preparing reference materials, managing time, reading and recording research materials. The results of sociological research are the basis for developing an Islamic religious education curriculum with a focus on introducing culture and the rules of science and technology by maximizing technological developments in learning activities. The world of Islamic religious education experiences a number of significant shifts periodically; Therefore, to compensate for this shift, it is necessary to develop an appropriate curriculum that is supported by a solid foundation. The direction of development goals is understood to ensure that appropriate principles must be applied when designing the Islamic religious education curriculum. The application of sociology in curriculum development contributes to the theoretical and practical development of the Islamic religious education curriculum and can increase authority in decision making regarding Islamic religious education regarding the Islamic religious education curriculum.